Sevoflurane post-conditioning attenuates traumatic brain injury-induced neuronal apoptosis by promoting autophagy via the PI3K/AKT signaling pathway - He H; Liu W; Zhou Y; Liu Y; Weng P; Li Y; Fu H (Dove Medical Press, 2018)
Hefan He,1 Weifeng Liu,1 Yingying Zhou,1 Yibin Liu,1 Peiqing Weng,1 Yasong Li,2 Huangde Fu3 1Department of Anesthesia, the Second Affiliated Hospital, Fujian Medical University, Quanzhou, Fujian, China; 2Department of Neurosurgery, the Second Affiliated Hospital, Fujian Medical University, Quanzhou, Fujian, China; 3Department of Neurosurgery, Affiliated Hospital of Youjiang Medical University for Nationalities, Baise, Guangxi, China Background: Sevoflurane post-conditioning exerts nerve-protective effects through inhibiting caspase-dependent neuronal apoptosis after a traumatic brain injury (TBI). Autophagy that is induced by the endoplasmic reticulum stress plays an important role in the secondary neurological dysfunction after a TBI. However, the relationship between autophagy and caspase-dependent apoptosis as well as the underlying nerve protection mechanism that occurs with sevoflurane post-conditioning following a TBI remains unclear. Methods: The Feeney TBI model was used to induce brain injury in rats. Evaluation of the modified neurological severity scores, measurement of brain water content, Nissl staining, and terminal deoxynucleotidyl transferase dUTP nick end labeling assay were used to determine the neuroprotective effects of the sevoflurane post-conditioning. Both immunofluorescence and Western blot analyses were used to detect the expression of autophagy-related proteins microtubule-associated protein 1 light chain 3-II and Beclin-1, pro-apoptotic factors, as well as the activation of the phosphatidylinositide 3-kinase/protein kinase B (PI3K/AKT) signaling pathway within the lesioned cortex. Results: Autophagy and neuronal apoptosis were activated in the lesioned cortex following the TBI. Sevoflurane post-conditioning enhanced early autophagy, suppressed neuronal apoptosis, and alleviated brain edema, which improved nerve function after a TBI (all P < 0.05). Sevoflurane post-conditioning induced the activation of PI3K/AKT signaling after the TBI (P < 0.05). The neuroprotective effects of sevoflurane post-conditioning were reversed through the autophagy inhibitor 3-methyladenine treatment. Conclusion: Neuronal apoptosis and the activation of autophagy were involved in the secondary neurological injury following a TBI. Sevoflurane post-conditioning weakened the TBI-induced neuronal apoptosis by regulating autophagy via PI3K/AKT signaling. Keywords: traumatic brain injury, sevoflurane post-conditioning, cell apoptosis, autophagy, PI3K/AKT signaling pathway